2018
DOI: 10.7759/cureus.3118
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Intervention Through Telephone Encounters for Blood Pressure Control by Residents in an Outpatient Resident Clinic

Abstract: IntroductionSixty-seven million Americans have hypertensionthat costs the nation $47.5 billion each year. The aim of this study was to determine if regular phone calls by residents helped achieve better blood pressure control.MethodsThe study was a randomized open-labeled study in a resident-run outpatient clinic in Rochester, New York. A total of 57 poorly controlled hypertensives in the clinic were divided into two groups. All the patients received scheduled phone calls once every two weeks for a total of 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…This telephone-based intervention has been described before and was found to be an effective method to improve compliance in patients with uncontrolled or newly diagnosed hypertension [ 24 ]. The RITE-BP trial also showed that blood pressure control was successfully achieved in patients through telephone calls and for 6 months follow up [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This telephone-based intervention has been described before and was found to be an effective method to improve compliance in patients with uncontrolled or newly diagnosed hypertension [ 24 ]. The RITE-BP trial also showed that blood pressure control was successfully achieved in patients through telephone calls and for 6 months follow up [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Higher BP reduction was associated with higher call engagement, possibly due to greater exposure to the intervention. Another study [ 49 ] demonstrated increased BP reductions with higher call engagement.…”
Section: Discussionmentioning
confidence: 99%